Evaluative Frameworks and Scientific Knowledge for Undergraduate STEM Students: An Illustrative Case Study Perspective. Issue 1 (2nd January 2021) - Mercer, Kate; Weaver, Kari D.
ABSTRACT: COVID-19 gives an important focal point to the increasingly complex and overwhelming amounts, types, and availability of information undergraduate STEM students are faced with. The world at large is being asked to seek information around serious infectious diseases and find information that can help facilitate decision-making in both personal and academic settings. Much of the available information lacks a fundamental scientific basis but is often masquerading as 'truth'. This is translated both into how society at large seeks information to make decisions, as well as how STEM undergraduate students are finding information to build their scientific skill set. This paper uses two case study examples of publications in scientific journals to examine the concept of using RADAR to determine validity. STEM librarians should focus on using evaluative frameworks as an initial launch point for critique, but a conversation must begin around how to encourage student realization of broader context and specifically awareness of what is still unknown.